Introduction: Symposium Limitarianism: Extreme Wealth as a Moral Problem - Timmer, Dick; Neuhäuser, Christian (Technische Universität Dortmund, 2022)
The growing concentration of wealth has acquired a new urgency in recent years. One particular view in this context is developed by Ingrid Robeyns in her ground-breaking work on limitarianism. According to this view, no one should have more than a certain amount of valuable goods, such as income and wealth. The contributors to this symposium, Brian Berkey, David Axelsen and Lasse Nielsen, Jessica Flanigan and Christopher Freiman, and Lena Halldenius, critically examine various aspects of limitarianism. In particular, they examine how limitarianism should be interpreted and developed as a principle of justice, on what reasons speak in favour and against limitarianism, and on how limitarianism relates to other principles of distributive justice. Our hope is that this symposium will contribute to the ongoing debate in political philosophy about the concentration of wealth and economic justice.
Ethical theory and moral practice;25(5)
Keywords: Limitarianism; Distributive Justice; Wealth; Billionaires; Robeyns; 100